Bersama Anwar ke penjara - Kamarazaman Yacob (Petaling Jaya, Selangor : Transgrafik, 1994)
Author's account on his years in prison with Anwar Ibrahim as political detainees during their student years.
Koleksi Sumbangan : Dr. Syed Husin Ali
In Malay.
Keywords: Anwar Ibrahim, -- Datuk Seri, -- 1947-; Politicians -- Malaysia -- Biography; Political prisoners -- Malaysia -- Biography; Prisons -- Malaysia